Muddied Waters: The Case for Mitigating Sediment and Nutrient Flux to Optimize Restoration Response in the Murray-Darling Basin, Australia - Gell, Peter A.; Reid, Michael A. (Frontiers in Ecology and Evolution, 2016)
The waters of the Murray Darling Basin, Australia, have endured multiple stressors for more than a century. Detectable salinisation impacts are evident from 1880 CE and elevated fluxes of sediments and nutrients are now widespread. Most wetlands examined paleolimnologically have shown increased sedimentation rates or have lost aquatic plant communities due to the shading effect of increased turbidity, prompting the observation that the waterways of the Murray Darling Basin are among ten Australian ecosystems most at risk from tipping points. This post-European heightened sediment flux threatens the potential ecological recovery from the application of scarce and expensive environmental water. Nutrients and fine sediments are implicated as drivers of regime shifts that advantage phytoplankton and inhibit the growth of productive macrophyte beds. However, with the river channels identified as likely sources of sediments and sediment-bound phosphorous, it remains possible that the documented ecological changes represent an ongoing response from continued doses from the River. Syntheses of multiple paleolimnological records provide evidence for the management focus to be on sediment supply to maximise the ecological benefit from environmental flow allocations. Here we use paleolimnology to examine in detail the nature and magnitude of the response in a subset of 17 wetlands, to propose means of optimising the ecological bounce from the release of river waters, encumbered with high doses of sediments and nutrients, to wetlands and floodplains.